THE EMPRICIAL IMPORTANCE OF HABIT FORMATION IN DSGE MODELS: A BAYESIAN INVESTIGATION FOR POLISH ECONOMY - Kuchta, Zbigniew (European Scientific Journal, ESJ, 2014)
In this paper I present the small scale DSGE model of staggered wage and price contracts with internal habit formation, where the utility from a current consumption is affected by the level of the consumer’s own past consumption. Internal habit formation seems to be a reasonable compromise between catching up with the Joneses, where the reference level of consumption is given by the consumption of representative agent and deep habits. In order to assess the empirical importance of habit formation I estimate and compare using Bayesian techniques two variants of DSGE model: one with habit formation and the other without habit formation. The estimation and comparison is based on quarterly data for Polish economy. The results suggest that model with habit formation is clearly favored by the data. However, obtained Bayes factor seems to be very low in comparison to results for other economies. Comparison of impulse response functions shows that introduction of habit formation has rather limited impact on propagation mechanisms. Moreover, obtained posteriors seem to be stable between these models.